Proceedings of the Ninth HDL (High-Density Lipoprotein) Workshop: Focus on Cardiovascular Disease. Issue 12 (December 2019) - Rodriguez, Annabelle; Trigatti, Bernardo L.; Mineo, Chieko; Knaack, Darcy; Wilkins, John T.; Sahoo, Daisy; Asztalos, Bela F.; Mora, Samia; Cuchel, Marina; Pownall, Henry J.; Rosales, Corina; Bernatchez, Pascal; et al.
Abstract : The HDL (high-density lipoprotein) Workshop was established in 2009 as a forum for candid discussions among academic basic scientists, clinical investigators, and industry researchers about the role of HDL in cardiovascular disease. This ninth HDL Workshop was held on May 16 to 17, 2019 in Boston, MA, and included outstanding oral presentations from established and emerging investigators. The Workshop featured 5 sessions with topics that tackled the role of HDL in the vasculature, its structural complexity, its role in health and disease states, and its interaction with the intestinal microbiome. The highlight of the program was awarding the Jack Oram Award to the distinguished professor emeritus G.S. Getz from the University of Chicago. The tenth HDL Workshop will be held on May 2020 in Chicago and will continue the focus on intellectually stimulating presentations by established and emerging investigators on novel roles of HDL in cardiovascular and noncardiovascular health and disease states.